Qualidade tecnológica e produtividade agroindustrial de cana-deaçúcar submetida a adubação com zinco - Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Buzetti, Salatiér; De Paula Garcia, Cássia Maria [UNESP]; Benett, Cleiton Gredson Sabin; De Carvalho Rodrigues, Mateus Augusto [UNESP]; Maestrelo, Paulo Ricardo [UNESP]; De Souza Celestrino, Thiago [UNESP]; De Niro Gazola, Rodolfo [UNESP] (Universidade Estadual de Londrina, 2013)
The technological quality and yield of the sugarcane crop can be prejudiced by expansion of the crop to areas of low fertility, which usually present low zinc contents in the soil. The deficiency of this nutrient can result in the reduction of tillering, shorter internodes and thinner stem. Thus, the objective of this work was to evaluate the effect of doses and sources of zinc applied in the planting furrow, in the technological quality and agroindustrial yield of the sugarcane (cane-plant and first cane-ratton) cultivated in a sandy texture soil with low zinc content, in Northwest of São Paulo state. The experiment was accomplished in an eutroferric Alfisol, in an agricultural area administered by Usina Vale do Paraná Sugar and Alcohol, in Suzanápolis - SP, Brazil. A randomized complete blocks design, with 4 repetitions, disposed in a factorial scheme 5x3, being: five doses of Zn (0; 2.5; 5.0; 7.5 e 10.0 kg ha-1) and three sources of Zn (FTE, Zn chelate and Zn sulfate) applied in the planting furrow. In the first cane-ratton, there were larger percentages of sucrose concentration (pol cane and pol juice) and juice purity for the chelate and sulfate of Zn, and larger percentage of juice reducing sugars for the FTE and sulfate of Zn. The agroindustrial yield of the sugarcane was not affected by increasing the zinc doses. Based on the indicators of technological quality (sucrose concentration, brix cane and total recoverable sugar) of the first cane-ratton, would be interesting the application between 4.0 and 5.0 kg ha-1 of Zn in the planting furrow, in the form of chelate or sulfate of Zn.
Technological quality and agroindustrial yield of sugarcane subject to zinc fertilization
Keywords: Micronutrient; Saccharum spp.; Sucrose concentration; Total recoverable sugar; Zinc sources